FORMATION OF EXPERIENCE OF REFLECTIVE ACTIVITY IN FUTURE TEACHERS IN THE PROCESS OF TEACHING - Zоkirov Sherzod Numonjon ugli (Western European Studies, 2024)
The article reveals important issues of formation and development of reflection in future teachers. The author includes a reflexive component in the content of training and considers the main techniques of reflexive thinking. In the context of reflexive learning, there is a shift in educational emphases towards the integration of cognitive and personal experience, that is, the task arises to perform the reverse operation: to introduce a personal context into a cognitive task and put students in a reflexive position in relation to the educational material, to fellow students and to themselves. Therefore, we include a reflexive component in the content of training future foreign language teachers, which provides for the formation of reflexive thinking techniques.
Keywords: reflective methods; retrospective reflection; current reflection